COMPARATIVE ANALYSIS OF THE EFFICIENCY OF MICROSERVICE AND MONOLITHIC ARCHITECTURES UNDER HIGH LOAD CONDITIONS - Michael Gevorgyan (American Journals Publishing, 2025)
The article presents a comparative analysis of the efficiency of microservice and monolithic architectures under high load conditions. The main focus is on such parameters as scalability, performance, fault tolerance, and infrastructure costs. The results show that microservice architecture provides higher stability and scalability under intensive loads, but its use is associated with increased operating costs and increased infrastructure complexity. At the same time, monolithic architecture demonstrates better performance under moderate load and is characterized by lower maintenance costs.
Keywords: Microservices, monolithic architecture, high load, scalability, performance, fault tolerance, DevOps, hybrid architectures.